"I Figure Singing and Playing Is the Same": Louis Armstrong and Barbershop Harmony. (2nd January 2017) - Hobson, Vic
ABSTRACT: Recent research has shown that the counterpoint of New Orleans jazz derives from the application of the principles of barbershop harmonization to the instruments of a jazz ensemble. This essay argues that what have become known as "blue notes" are the result of tenor and baritone voice leading in a barbershop quartet. When these principles are applied to an improvised solo a blues inflected solo results. I explore how Louis Armstrong used barbershop principles in 12-bar-blues recordings of the 1920s in relation to dominant harmony, and that by the application of these principles, Armstrong introduced altered intervals (ninths and fifths) to his solos.